Stress-Related Mental Health Symptoms in Coast Guard: Incidence, Vulnerability, and Neurocognitive Performance - Servatius, Richard J.; Handy, Justin D.; Doria, Michael J.; Myers, Catherine E.; Marx, Christine E.; Lipsky, Robert; Ko, Nora; Avcu, Pelin; Wright, W. Geoffrey; Tsao, Jack W. (Frontiers in Psychology, 2017)
U.S. Coast Guard (CG) personnel face occupational stressors (e.g., search and rescue) which compound daily life stressors encountered by civilians. However, the degree CG personnel express stress-related mental health symptoms of posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) is understudied as a military branch, and little is known concerning the interplay of vulnerabilities and neurocognitive outcomes in CG personnel. The current study addressed this knowledge gap, recruiting 241 active duty CG personnel (22% female) to assess mental health, personality, and neurocognitive function. Participants completed a battery of scales: PTSD Checklist with military and nonmilitary prompts to screen for PTSD, Psychological Health Questionnaire 8 for MDD, and scales for behaviorally inhibited (BI) temperament, and distressed (Type D) personality. Neurocognitive performance was assessed with the Defense Automated Neurobehavioral Assessment battery. Cluster scoring yielded an overall rate of PTSD of 15% (95% CI: 11-20%) and 8% (95% CI: 3-9%) for MDD. Nonmilitary trauma was endorsed twice that of military trauma in those meeting criteria for PTSD. Individual vulnerabilities were predictive of stress-related mental health symptoms in active duty military personnel; specifically, BI temperament predicted PTSD whereas gender and Type D personality predicted MDD. Stress-related mental health symptoms were also associated with poorer reaction time and response inhibition. These results suggest rates of PTSD and MDD are comparable among CG personnel serving Boat Stations to those of larger military services after combat deployment. Further, vulnerabilities distinguished between PTSD and MDD, which have a high degree of co-occurrence in military samples. To what degree stress-related mental healthy symptoms and attendant neurocognitive deficits affect operational effectiveness remains unknown and warrant future study.